2009
DOI: 10.1002/hyp.7421
|View full text |Cite
|
Sign up to set email alerts
|

Temporal sampling strategies and uncertainty in calibrating a conceptual hydrological model for a small boreal catchment

Abstract: Abstract:How much data is needed for calibration of a hydrological catchment model? In this paper we address this question by evaluating the information contained in different subsets of discharge and groundwater time series for multi-objective calibration of a conceptual hydrological model within the framework of an uncertainty analysis. The study site was a 5Ð6-km 2 catchment within the Forsmark research site in central Sweden along the Baltic coast. Daily time series data were available for discharge and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 36 publications
12
70
0
Order By: Relevance
“…Limited information content in discharge time series was also demonstrated by Juston et al (2009) and Seibert and Beven (2009), who found that calibration using a small fraction of data points chosen at hydrologically informed times was comparable to when the whole time series was used. We chose R eff for comparison with the FDC-calibration as it is sensitive to timing errors, well-known and commonly used.…”
Section: Discussionmentioning
confidence: 94%
“…Limited information content in discharge time series was also demonstrated by Juston et al (2009) and Seibert and Beven (2009), who found that calibration using a small fraction of data points chosen at hydrologically informed times was comparable to when the whole time series was used. We chose R eff for comparison with the FDC-calibration as it is sensitive to timing errors, well-known and commonly used.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, Wagener et al (2003) identify inconsistencies in the structure of a rainfall-runoff model by highlighting instabilities of the optimal values of the parameters between periods with and without rainfall events. In contrast, Juston et al (2009) found that data subset of their input data (from daily to quaterly sampling intervals) can provide very similar constraints on model calibration and parameter identification.…”
Section: What Hydrological Good Sense Suggestsmentioning
confidence: 97%
“…[2] The appropriate length of observation data for effective calibration of continuous hydrologic models has been a challenging research question [Andreassian et al, 2001;Gupta and Sorooshian, 1985;Juston et al, 2009;Perrin et al, 2007;Singh and Bardossy, 2012;Vrugt et al, 2006;Xia et al, 2004;Yapo et al, 1996]. In general, longer calibration periods are deemed more robust and reliable in identifying the model parameters and quantifying their uncertainty [Perrin et al, 2007].…”
Section: Motivation and Objectivementioning
confidence: 99%